Against Lawton's Contingency Thesis; or, Why the Reported Demise of Community Ecology Is Greatly Exaggerated. Issue 5 (December 2015) - Linquist, Stefan
Abstract : Lawton's contingency thesis (CT) states that there are no useful generalizations ("laws") at the level of ecological communities because these systems are especially prone to contingent historical events. I argue that this influential thesis has been grounded on the wrong kind of evidence. CT is best understood in Woodward's terms as a claim about the instability of certain causal dependencies across different background conditions. A recent distinction between evolution and ecology reveals what an adequate test of Lawton's thesis would look like. To date, CT remains untested. But developments in genome-level ecology and molecular ecology point in promising directions.